2003
DOI: 10.1207/s15327752jpa8002_02
|View full text |Cite
|
Sign up to set email alerts
|

Four Studies Extending the Utility of the Schwartz Outcome Scale (SOS-10)

Abstract: The Schwartz Outcome Scale (SOS-10; Blais et al., 1999) is a brief, cost free, and easy to administer assessment device designed to measure a broad domain of psychological health. The 4 studies using the SOS-10 reported here extend the initial reliability and validity studies beyond psychiatric patients in a hospital setting to examine (a) test-retest reliability in a college student population, (b) concurrent validity with college students using an indirect technique assessing maladjustment, (c) concurrent va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
60
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 22 publications
2
60
0
Order By: Relevance
“…Further, the present study shows that the measure is not only good at assessing treatment outcome in a clinical population but can also be used to assess quality of life and psychological well-being in a non-clinical population as well as further enhancing the measure's utility for use in research with non-clinical samples. As Young et al (2003) state, mental health researchers and practitioners who are apprehensive about utilizing quality of life/ outcome measures that are intrusive or expensive would do well to consider the Schwartz Outcome Scale. The SOS-10 is advantageous because it is short and easy to score and administer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, the present study shows that the measure is not only good at assessing treatment outcome in a clinical population but can also be used to assess quality of life and psychological well-being in a non-clinical population as well as further enhancing the measure's utility for use in research with non-clinical samples. As Young et al (2003) state, mental health researchers and practitioners who are apprehensive about utilizing quality of life/ outcome measures that are intrusive or expensive would do well to consider the Schwartz Outcome Scale. The SOS-10 is advantageous because it is short and easy to score and administer.…”
Section: Discussionmentioning
confidence: 99%
“…Psychometric analysis indicates that the SOS-10 is internally consistent (Cronbach's alpha = 0.96), with item-scale correlations ranging from 0.74 to 0.90. Total scores from the SOS-10 have been shown to be related to scores for measures of mental health, fatigue, life satisfaction, desire to live, positive and negative affect, self-esteem, hopelessness and mental health, demonstrating the construct validity of this measure (Blais et al, 1999;Dragomirecka, Lenderking, Motlova, Goppoldova, & Selepova, 2006;Laux & Ahern, 2003;Rivas-Vazquez et al, 2001;Young, Waehler, Laux, McDaniel, & Hilsenroth, 2003) Recent research (Dragomirecka et al, 2006;Rivas-Vazquez et al, 2001;Young et al, 2003) of the SOS-10 ( Blais et al, 1999) has shown that the measure is well-suited for tapping quality of life and psychological well-being in a number of different settings and with diverse patient populations. The SOS-10 also appears to be a valid measure of general life satisfaction, well-being and psychological health.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…SOS-10 is a psychometrically sound, wellvalidated, 10-item self-report measure of psychological well-being and distress (Blais et al, 1999;Young, Laux, Waehler McDaniel, & Hilsenroth, 2003). The SOS-10 is sensitive to early treatment change (Blais, et al, 1999;Hilsenroth, Ackerman, & Blagys, 2001).…”
Section: Schwartz Outcome Scale-10 (Sos-10)mentioning
confidence: 99%
“…The SOS-10 has been found to have strong internal consistency (Cronbach alpha = .96) and item-to-scale correlations ranging from .74 to .90 (Blais et al, 1999). Furthermore, the SOS-10 has demonstrated good construct validity, as it has been associated with measures of mental health (Blais et al, 1999;, depression and anxiety (Dragomirecka et al, 2006), substance use (Laux & Ahern, 2003), maladjustment and distress in college students (Young et al, 2003) and the five-factor model (Haggerty, Blake, Naraine, Siefert, & Blais, 2010). The current study evidenced good internal consistency of the scale (Cronbach's alpha of .87).…”
Section: Schwartz Outcome Scale-10 (Sos-10)mentioning
confidence: 99%